2020
DOI: 10.3390/antiox9040272
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Biofortification Impacts the Nutritive Value, Polyphenolic Content, and Bioactive Constitution of Variable Microgreens Genotypes

Abstract: Selenium (Se) is considered essential for human nutrition as it is involved in the metabolic pathway of selenoproteins and relevant biological functions. Microgreens, defined as tender immature greens, constitute an emerging functional food characterized by overall higher levels of phytonutrients than their mature counterparts. The nutraceutical value of microgreens can be further improved through Se biofortification, delivering Se-enriched foods and potentially an enhanced content of bioactive compounds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
68
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 74 publications
12
68
7
Order By: Relevance
“…Seedlings of edible vegetables supplemented with selenate seem to preferentially accumulate organic Se, and their nutritional value is generally ameliorated by Se enrichment (D'Amato et al 2018b(D'Amato et al 2020Islam et al 2020;Pannico et al 2020). In fact, Ávila et al (2014) screened Se-enriched cultivars from the six largely consumed Brassica vegetables and found that all were able to accumulate MeSeCys and contained higher levels of GLS, especially glucoraphanin.…”
Section: Effects Of Se-biofortification On Se-s Crosstalk and Accumulmentioning
confidence: 99%
“…Seedlings of edible vegetables supplemented with selenate seem to preferentially accumulate organic Se, and their nutritional value is generally ameliorated by Se enrichment (D'Amato et al 2018b(D'Amato et al 2020Islam et al 2020;Pannico et al 2020). In fact, Ávila et al (2014) screened Se-enriched cultivars from the six largely consumed Brassica vegetables and found that all were able to accumulate MeSeCys and contained higher levels of GLS, especially glucoraphanin.…”
Section: Effects Of Se-biofortification On Se-s Crosstalk and Accumulmentioning
confidence: 99%
“…Microgreens are also regarded as fresh "super foods" [4,9,10] due to their innate fortification with plant secondary metabolites [9,[11][12][13]. Additionally to carotenoids, ascorbic acid, phylloquinone, γ-tocopherols, and phenolic compounds, microgreens are also a source of macro and micro-minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to carotenoids, ascorbic acid, phylloquinone, γ-tocopherols, and phenolic compounds, microgreens are also a source of macro and micro-minerals. Such nutritive and functional values enhance human diet and prevent a range of common diseases [4,9,10,12,14]. Indeed, microgreens enclose a greater load of essential phytonutrients compared to their mature counterparts [3,4,6,10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the duration of the growing cycle of microgreens is intermediate between sprouts and "baby leaf" vegetables. Thanks to their flexibility in cultivation, several growing techniques have been applied to microgreens in order to modulate the content of nutritional compounds to obtain tailored food products [13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%